Medidas de seguridad en la obra denominado “embarcadero del puerto de Tahuishco de la ciudad de Moyobamba” - Herrera Medina, Julio César (2013)
The present work looked for fortify the work academy train of the Environment Engineer future, specialized in Residual Solid Handling specifying industrial waste treatment topic; located in the province and district of Moyobamba The San Martin town, which took information about the land and at the same time diagnosed the actual situation of Residual Sol id Handling of this company. Also looked for, sensitized, consciousness and train to workers of the Agricultura!. in topics relatad to industrials and domestic Residual Solid Handling also it made train through topics of formal and informal education, which gave good results because of help and collaboration of the people of Pampa Hermosa in everything. To end it got basic information about to start any project about Residual Solid Handling either for the government or private. For this reason 1 am pleasure, had put in the Agricultura! Company work, that probably had sorne mistakes, but after all lt had willingness and wish about todo things well and better. The present work looked for fortify the professional academy train of the Environment Engineer future, specialized in Residual Solid Handling specifying industrial waste treatment topic; so this professional practica was developed in the Agricultura! located in the province and district of Moyobamba In the San Martin town, which took information about the land and at the same time diagnosed the actual situation of Residual Sol id Handling of this company. Also looked for, sensitized, consciousness and train to workers of the Agricultura! in topics relatad to industrials and domestic Residual Solid Handling also it made train through topics of formal and informal education, which gave good results because of help and collaboration of the people of Puerto de Tuahuishco in everything . To end it got basic information about to start any project about Residual Solid Handling either for the government or private. For this reason 1 am pleasure, had put in the Agricultura! Company this work, that probably had sorne mistakes, but after all lt had willingness and wish about to do things well and better.